A Chart for quick designing of four types of field channels for workers in soil conservation - Agarwal, S G (Journal of Soil and Water Conservation, 2022)
Proper water disposal system is the key factor to decide the success of Soil Conservation Planning of a watershed. Full consideration has to be given to the existing condi- tions of watershed, rainfall, runoff, water utilization, economy and other such factors while planning, design- ing and executing field channels for their accuracy. A scientifically designed channel or diversion ditch is one which can safely carry the maximum expected runoff at a non-erosive and non- silting velocity. The life and economy in maintenance of channel largely depends upon the velocity which is attained by flowing runoff in it. If the velocity is too high it may start caving and eroding the channel surface, which ultimately may take a form of gully, and if the velocity is too low it may result in silting the channel. In both these cases there will be a regular expenditure in its maintenance.